Moving Mountains of A1c and Weight in T2D with oral GLP-1RA – More is More - Sukor, Norlela (International Journal of Human and Health Sciences (IJHHS), 2024)
Diabetes mellitus is a serious worldwide public health issue, posing a significant global burden on both public health and socioeconomic development. Based on the data from our National Registry Report 2020, among all the diabetes patients, 80.00% had hypertension and 75.72% had dyslipidemia. One of the most concerning data is, 84% of them are overweight or obese. This shows that T2DM patients are prone to have other types of complications other than uncontrolled glycemic level. Multiple diabetic medications are readily available but previously, GLP-1RA was only available in injectable formulation, making patients hesitant to start this therapy. Oral semaglutide is the first-ever oral GLP-1RA product for T2DM treatment and has become a favorable therapeutic option due to its holistic approach in addressing the pathophysiological defects of T2D. Oral Semaglutide has been beneficial not only for glycemic management but also cardiorenal risk reduction and weight management. Many of the guidelines globally and locally are advocating the use of GLP-1 RA early in treatment due to its robust data. Oral semaglutide is available in 3 strengths: 3mg, 7mg, and 14mg. Nevertheless, it is essential to slowly titrate up the dose to 14 mg to achieve the maximal benefit as shown by the PIONEER clinical trials. Prof Dr Norlela will illustrate the remarkable innovation and advantage of this peptide in a pill and share her personal experience using oral semaglutide during this lunch symposium. International Journal of Human and Health Sciences Supplementary Issue 01: 2024 Page: S7